An investigation on the role of learning organization in the realization of organizational learning based Marquart model: A case study of Islamic Azad University, Neyshabur branch - Ahmad Nategh Golestan; Seyed Morteza Ghayour Baghbani (Management Science Letters)
During the past few years, there has been increasing interest in identifying the strengths and weaknesses of learning organizations (LO) in universities. The theoretical basis of this study was based on a comprehensive and systematic approach to learning organization proposed by Michael Marquardt. The aim of this study was to evaluate the benefit of Islamic Azad University, Neyshabur branch as educational characteristics in terms of LO characteristics according to the science and technology dimensions. The study population included all faculty members of Islamic Azad University Neyshabur branch, 90 university professors were selected by simple random sampling, and they completed the questionnaires of the survey. The research instruments included a researcher-made questionnaire based on the Marquardt-reviewed literature and consultation with experts. The questionnaire included 50 items with a Likert scale of five degrees. Validity of the questionnaire was affirmed by calculating Cronbach's alpha coefficient. To test the hypothesis, paired t-student tests were used and the results indicated that the status of Islamic Azad University in terms of LO characteristics was significantly different from the desirable level.